2017
DOI: 10.1590/1678-4685-gmb-2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genetic diversity of the giant anteater (Myrmecophaga tridactyla: Myrmecophagidae, Pilosa) in Brazil

Abstract: The giant anteater (Myrmecophaga tridactyla, Pilosa, Linnaeus 1758) belongs to the mammalian order Pilosa and presents a large distribution along South America, occupying a great variety of habitats. It is listed in the IUCN Red List of threatened species as Vulnerable. Despite threatened, there is a lack of studies regarding its genetic variability. The aim of this study was to examine the genetic diversity and patterns of genetic structure within remaining populations. We analyzed 77 individuals from seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
15
2
Order By: Relevance
“…For Myrmecophaga , Clozato et al (2017) did not detect significant spatial genetic structure in Brazil, as we did in South America. One biological condition that could help to create inexistent spatial genetic structure in the giant anteater is the relatively high dispersion capacity, at least, of males.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…For Myrmecophaga , Clozato et al (2017) did not detect significant spatial genetic structure in Brazil, as we did in South America. One biological condition that could help to create inexistent spatial genetic structure in the giant anteater is the relatively high dispersion capacity, at least, of males.…”
Section: Discussioncontrasting
confidence: 53%
“…For M. tridactyla , Collevatti et al (2007) reported on the genetic structure, relatedness, and mating strategy of a population in the Emas National Park, Brazil, based on variability at five microsatellite loci, which all displayed low levels of polymorphism. Clozato et al (2017) also analyzed 77 individuals from seven populations in four Brazilian biomes and sequenced two mitochondrial (mt) markers (control region and cyt b ) and two nuclear markers ( AMELY and RAG2 ). They found high genetic diversity within several of the populations with signs of population expansion and found significant population differentiation between the Cerrado and Pantanal populations with those from the Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been performed to evaluate population dynamics and the genetic variability of giant anteater populations (Clozato et al., 2017; Collevatti et al., 2007). Garcia et al (2005) developed six species‐specific microsatellite primers and evaluated allelic diversity of markers from fifteen individuals (eight animals that had been run over in the states of São Paulo and Mato Grosso, and seven that had been collected in the state of Goiás).…”
Section: Discussionmentioning
confidence: 99%
“…There is a tendency for the remaining populations of M. tridactyla to become progressively more isolated, which, in turn, further increases their vulnerability and leads to various cases of local extinction. Some of the species’ biological characteristics may lead to low rates of population growth: a low metabolic rate and low thermoregulatory capacity, limited reproductive potential, prolonged parental care, a long gestation period, and solitary habits (Clozato et al., 2017). The species is a frequent victim of roadkills, as well as of fires caused by sugar cane crop burning and prolonged periods of drought.…”
Section: Introductionmentioning
confidence: 99%
“…Its solitary habits, low fecundity, long gestation time, and relatively high generation time ( Eisenberg and Redford, 1999 ) added to a specialist diet ( McNab, 1984 ), making this species more vulnerable and threatened in anthropic scenarios ( Desbiez et al, 2020 ). Within the distribution area of the giant anteater, mitochondrial haplogroups have been described, separating a population in the Amazon Forest from another group represented by individuals from the Cerrado and Pantanal biomes ( Clozato et al, 2017 ). Although two studies using local populations have already been published, little is known about the consequences on the genetic variation in highly anthropized regions of these vulnerable animals in Brazil.…”
Section: Introductionmentioning
confidence: 99%